PENGARUH PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, GOVERNANCE PADA NILAI PERUSAHAAN - Nanda, Ni Kadek Satya; Ratnadi, Ni Made Dwi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.10.TAHUN.2024DO - 10.24843/EEB.2024.v13.i10.p19, 2024)
The company's long-term objective is to promote shareholder welfare by enhancing its value. The purpose of this study is to analyze the impact of ESG, environmental, social, and governance factors on firm value. This study focused on all firms listed on the Indonesia Stock Exchange from 2020 to 2022. The sample for this study was determined using a purposive sampling strategy, namely organizations with an ESG score evaluation from Thomson Reuters, with a sample size of 150 observations. The data was analyzed using multiple linear regression. The findings of this study suggest that ESG disclosure has no influence on business value. Each ESG factor has various results. Each ESG factor has distinct findings; disclosure of environmental and governance aspects has no influence on firm value, however disclosure of social aspects increases firm value. This study gives theoretical implications for stakeholder theory, demonstrating that by exposing positive social characteristics, corporations may develop positive connections and earn the trust of stakeholders, so improving the company's reputation and increasing its value. This study's practical implications include that investors are more likely to respond to firms that disclose social issues.